The O-Ring Theory of Economic Development - Kremer, M. (Quarterly Journal of Economics, 1993)
This paper proposes a production function describing processes subject to mistakes in any of several tasks. It shows that high-skill workers—those who make few mistakes—will be matched together in equilibrium, and that wages and output will rise steeply in skill. The model is consistent with large income differences between countries, the predominance of small firms in poor countries, and the positive correlation between the wages of workers in different occupations within enterprises. Imperfect observability of skill leads to imperfect matching and thus to spillovers, strategic complementarity, and multiple equilibria in education.